Characterization of ATPase Activity of P2RX2 Cation Channel - Mittal, Rahul; Grati, M'hamed; Sedlacek, Miloslav; Yuan, Fenghua; Chang, Qing; Yan, Denise; Lin, Xi; Kachar, Bechara; Farooq, Amjad; Chapagain, Prem; Zhang, Yanbin; Liu, Xue Z. (Frontiers in Physiology, 2016)
P2X purinergic receptors are plasma membrane ATP-dependent cation channels that are broadly distributed in the mammalian tissues. P2RX2 is a modulator of auditory sensory hair cell mechanotransduction and plays an important role in hair cell tolerance to noise. In this study, we demonstrate for the first time in vitro and in cochlear neuroepithelium, that P2RX2 possesses the ATPase activity. We observed that the P2RX2 V60L human deafness mutation alters its ability to bind ATP, while the G353R has no effect on ATP binding or hydrolysis. A non-hydrolysable ATP assay using HEK293 cells suggests that ATP hydrolysis plays a significant role in the opening and gating of the P2RX2 ion channel. Moreover, the results of structural modeling of the molecule was in agreement with our experimental observations. These novel findings suggest the intrinsic ATPase activity of P2RX2 and provide molecular insights into the channel opening.